Problem 2.4

A First Course in String Theory

.

2.4 Lorentz transformations as matrices

A matrix L that satisfies (2.46) is a Lorentz transformation. Show the following.

(b) If \displaystyle{L} is a Lorentz transformation so is the inverse matrix \displaystyle{L^{-1}}.

(c) If \displaystyle{L} is a Lorentz transformation so is the transpose matrix \displaystyle{L^{T}}.

~~~

(b)

\displaystyle{   \begin{aligned}   (\mathbf{A}^\mathrm{T})^{-1} &= (\mathbf{A}^{-1})^\mathrm{T} \\  L^T \eta L &= \eta \\  \eta &= [L^T]^{-1} \eta L^{-1} \\  [L^T]^{-1} \eta L^{-1} &= \eta \\  [L^{-1}]^T \eta L^{-1} &= \eta \\  \end{aligned}}

.

(c)

\displaystyle{   \begin{aligned}   L^T \eta L &= \eta \\  (L^T \eta L)^{-1} &= (\eta)^{-1} \\  L^{-1} \eta^{-1} (L^T)^{-1} &= \eta \\  L^{-1} \eta (L^T)^{-1} &= \eta \\  \eta &= L \eta L^T \\  L \eta L^T &= \eta \\  \end{aligned}}

— Me@2020-12-21 04:24:33 PM

.

.

2020.12.21 Monday (c) All rights reserved by ACHK